Design Sustainability for Battery Packaging to Increase Customer Satisfaction - Aissyah Lathifah Adriyanti; Taufik Roni Sahroni (Journal of Engineering)
An automotive battery, also known as a car battery, is a device that provides electrical energy to start a vehicle’s engine; it uses chemical reactions between lead (Pb) and other chemicals to generate electricity. The automotive industry has been receiving positive feedback from consumers, and the industry has been striving to improve the quality of its product packaging, which protects the battery and facilitates its distribution. The research aims to increase customer satisfaction in the automotive industry by creating better battery packaging design. The research employs a range of methods to achieve this goal, including conducting an initial survey with customers who have purchased and used car batteries to identify problems, 3D computer-aided design (CAD) to create design packaging development, life-cycle assessment (LCA) to measure the environmental impact of various materials and contains sustainability analysis, and finite element analysis (FEA) simulation of the packaging corrugated paper using SolidWorks 2021 software, and lastly, a customer feedback survey is conducted to assess the attributes of packaging development. The design criteria prioritize green materials, ergonomics, durability, reliability, and ease of use. In conclusion, the study recommends the use of corrugated paper for battery packaging in the automotive industry. The corrugated paper has proven to be an ecofriendly and sustainable material that provides excellent protection for the battery while also being easy to handle and use.